The Impact of Climate Change on the Potential Habitat Distribution of Eggs and Larvae of the Liza haematocheilus and Harpadon nehereus in the Coastal Waters of Zhejiang Province - Yuelian He; Rijin Jiang; Rui Yin; Peng Zhao; Mengyuan Zhang; Jinqing Wang (Journal of Marine Science and Engineering, 2026)
In recent years, climate change has increasingly shaped the potential habitat distribution of marine fishes, rendering this topic a focal area in marine ecology and biogeographical research. Using the MaxEnt modeling approach, this study projects the current and future potential habitats of eggs and larvae of two ecologically and economically important coastal species, the Liza haematocheilus and the Harpadon nehereus, across the nearshore waters of Zhejiang Province. Distribution records of early life stages and key environmental variables were integrated to model suitability under present-day conditions and three Shared Socioeconomic Pathway–Representative Concentration Pathway climate scenarios: SSP2-4.5, SSP3-7.0, and SSP5-8.5. Results identify sea surface salinity, surface current velocity, and sea surface temperature as the primary drivers of habitat suitability for Liza haematocheilus early-life stages; in contrast, chlorophyll-a concentration emerges as an additional significant predictor for Harpadon nehereus, alongside the aforementioned three variables. Under contemporary climatic conditions, high-suitability habitats for Liza haematocheilus eggs and larvae are predominantly concentrated in estuarine and island-adjacent nearshore zones, constituting 40.76% of the total predicted suitable area. For Harpadon nehereus, high-suitability areas are broadly distributed across nearshore shelf waters, representing 65.57% of its total modeled suitable habitat. Projected under future scenarios, the largest absolute increase in high-suitability area for Liza haematocheilus occurs under SSP3-7.0 in the 2050s (+0.38 × 104 km2), whereas Harpadon nehereus exhibits its greatest expansion under SSP5-8.5 in the 2090s (+0.45 × 104 km2). Collectively, the total suitable habitat area for Liza haematocheilus is projected to expand across all three scenarios, while that of Harpadon nehereus remains relatively stable overall—yet its high-suitability fraction increases markedly under high-emission, high-warming conditions. These findings suggest that ongoing climate warming may facilitate range expansion and enhanced nursery habitat availability for both species in Zhejiang’s coastal zone, positioning them as potential ecological beneficiaries of regional climate change.